1974
DOI: 10.1111/j.1533-8525.1974.tb00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Women and Men Among Black and White College Students

Abstract: Rainwater's assertion that blacks have low self‐evaluations because they receive more negative evaluations from other blacks than whites receive from other whites is challenged here by reference to Heiss and Owens evidence that negative self evaluation among blacks is limited to work‐related traits. Substantial support was found for our major hypotheses that, compared to whites, (1) blacks would report more negative evaluation of “most men” but not of “most women” (since the provider role is traditionally ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

1978
1978
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
11
2
Order By: Relevance
“…Recent research solidifies the notion that Black girls, adolescents, and women have high levels of self-esteem (Crain & Weisman, 1972;DeFrancisco & Chatham-Carpenter, 2000;Hoelter, 1983;Myers, 1975Myers, , 1980Richman, Clark, & Brown, 1985;Rosenberg & Simmons, 1972;Turner & Turner, 1974, 1982. Somehow, in constructing their lives, Black females have developed implicit attitudes and explicit behaviors that enable them to possess internal sources of self-esteem that are socially rooted (Gibbs & Fuery, 1994).…”
Section: Influences Of a Healthy Self-esteemmentioning
confidence: 66%
See 1 more Smart Citation
“…Recent research solidifies the notion that Black girls, adolescents, and women have high levels of self-esteem (Crain & Weisman, 1972;DeFrancisco & Chatham-Carpenter, 2000;Hoelter, 1983;Myers, 1975Myers, , 1980Richman, Clark, & Brown, 1985;Rosenberg & Simmons, 1972;Turner & Turner, 1974, 1982. Somehow, in constructing their lives, Black females have developed implicit attitudes and explicit behaviors that enable them to possess internal sources of self-esteem that are socially rooted (Gibbs & Fuery, 1994).…”
Section: Influences Of a Healthy Self-esteemmentioning
confidence: 66%
“…Porter and Washington (1979) contend that this component is crucial to the selfesteem of African Americans. Some theorists initially believed that Blacks blame themselves for their failures (Heiss & Owens, 1972;Pettigrew, 1964;Turner & Turner, 1974, 1982, especially in relation to socioeconomic issues. But what they found was that African Americans actually attribute the cause of their shortcomings to external forces, such as racial discrimination, that they could not control (Crain & Wiessman, 1972;Gurin & Epps, 1975;Hughes & Demo, 1989).…”
Section: Refuting the Principles Of Self-esteemmentioning
confidence: 99%
“…Riley and Napier studied the 1976 NAEP data for 17-year olds and found that the demographic variable sex accounted for only 2% of the variance in cognitive achievement (1982). With the exception of the findings of Kelly and Wingrove (1975), other studies found black females demonstrating lower levels of educational aspirations (Gurin & Gaylord, 1976;Turner & Turner, 1975;Gilmartin, 1976;and Teahan, 1974).…”
Section: Introductionmentioning
confidence: 87%
“…It does appear that the practice of belittling and dehumanizing black males has been continued in a subtler manner by television's producers and writers who have now cast black women in the role of belittlers of black men. Although there is some evidence that black women do negatively stereotype black men (Turner & Turner, 1974), this behavior is not as absolute as that depictcd on T.V.…”
Section: Derogation and Ridicule Of Black Menmentioning
confidence: 93%